Religious life surrounding three thermal springs in ancient Dacia - Jarych, Adam Jakub (Acta Archaeologica Lodziensia, 2019)
The paper deals with the three most important thermal springs in ancient Dacia, on which part of the religious life of the province centred. The available source material makes it possible to determine which deities received the most worship among the visitors enjoying the pleasures of Ad Mediam, Ad Aquas, and Germisara. The collected sources also let us find out what groups of the province’s inhabitants were treated in those extremely popular centres, referred to by many researchers as ancient spa resorts.